Pengaruh Gugus Metil pada Posisi Para dari Turunan 2-(P-Klorofenil)-Kuinazolin-4(3h)-On terhadap Aktivitas Analgesik pada Mencit - Soeliono, Ivonne; Budiati, Tutuk; Tamayanti, Wahyu Dewi (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
This study has evaluated analgesic activity of 3-benzylideneamino-2-(p-chlorophenyl)-quinazoline-4(3H)-one and 3-(4-methylbenzylideneamino)-2-(p-chlorophenyl)-quinazoline-4(3H)-one. The purposes of this study were to measure analgesic activity, to compare their analgesic potency against mefenamic acid, and to determine the effect of methyl substituent addition on para position of 3-benzylideneamino-2-(p-chlorophenyl)-quinazoline-4(3H)-one toward analgesic activity in mice. Analgesic activity evaluation was performed in mice using writhing test method with acetic acid as pain inducer. The significance difference of writhing frequencies between each group was tested using one-way ANOVA followed by Tukey HSD test as a post-hoc test. The statistic comparison results showed that the synthesized drug and the reference compound had an analgesic activity, in which the synthesized drug had the same analgesic potency with mefenamic acid on the same dosage, and the addition of methyl substituent on para position of 3-benzylideneamino-2-(p-chlorophenyl)-quinazoline-4(3H)-one did not lead to the increase of analgesic activity in mice.